ANALISIS POLA PENGAJARAN PESERTA DIDIK BERKEBUTUHAN KHUSUS DI KELAS V SDN 117 PEKANBARU - Tiatil Mahfudzoh; Jesi Alexander Alim; Neni Hermita (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the teaching patterns of students with special needs (PDBK) in fifth grade at SDN 117 Pekanbaru in the context of inclusive education. The background of this research is the existence of teachers who apply a uniform teaching pattern for all students without considering the special needs of PDBK. This research uses a descriptive qualitative approach with a case study method. The subjects of the study are fifth-grade homeroom teachers without special assistance teachers. Data collection techniques are conducted through observation, interviews, and documentation. This research focuses on four main indicators of teaching patterns according to Lestariningrum, namely: lesson planning (RPPM and RPPH), implementation/learning process that uses a student-centered approach for PDBK, assessment, and reporting of PDBK learning outcomes. The research results indicate that teachers have implemented most of the indicators well. In conclusion, the teaching patterns applied have led to inclusive education practices, although they are not yet fully optimal. This study contributes to the development of adaptive teaching strategies and is expected to serve as a reference for teachers in designing learning that is responsive to the individual needs of students.